Comparing microleakage in root canals obturated with nanosilver coated gutta-percha to standard gutta-percha by two different methods - yazdan shantiaee; Farzin Maziar; Omid Dianat; Faranak Mahjour (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2011)
INTRODUCTION: Favorable apical seal of root filling materials is a crucial factor for a successful root canal treatment. The aim of this in vitro study was to compare bacterial and dye microleakage of two root canal filling materials including standard gutta-percha and nanosilver coated gutta-percha, and to evaluate the agreement between results of these two methods. MATERIALS & METHODS: Fifty-eight extracted single-rooted teeth were randomly divided into two experimental groups of 26 each, and two control groups of three each. After decoronation, root canals were instrumented by crown-down technique. Obturation was conducted using standard gutta-percha in one of experimental groups and nanosilver-coated gutta-percha in another group. AH26 sealer was used as the sealer in both experimental groups. Bacterial leakage was investigated after 60 days using Enterococcus (E.) faecalis microbial strains, and dye leakage was assessed during 72 hours using 1% methylene blue. The data were statistically analyzed by Chi-square test, Kaplan-Meier survival analysis, and Cohen's Kappa. RESULTS: There was 84% bacterial leakage in standard gutta-percha group and 76% in nanosilver gutta-percha group. Complete dye leakage occurred in 24% and 27% of standard and nanosilver gutta-percha groups, respectively. The above difference between groups was not significant. In the samples with leakage, recorded times of leakage were not significantly different. There was no significant measure of agreement between dye and bacterial penetration along root-end fillings. CONCLUSION: There was a poor agreement between dye and bacterial leakage methods. Leakage results produced by nanosilver gutta-percha were comparable to those by standard gutta-percha. Considering the antibacterial effects of nanosilver coated gutta-percha, use of this type of gutta-percha might be more efficacious in endodontic treatments.